1994
DOI: 10.1002/jmr.300070108
|View full text |Cite
|
Sign up to set email alerts
|

Structural and physicochemical analysis of the reaction between the anti‐lysozyme antibody D1.3 and the anti‐idiotopic antibodies E225 and E5.2

Abstract: The reaction between the mouse (BALB/c) anti-idiotopic monoclonal antibodies E225 and E5.2 and idiotopes on the (BALB/c) anti-lysozyme monoclonal antibody D1.3 has been characterized by titration calorimetry, by equilibrium sedimentation and by the determination of binding association and dissociation rates. The reaction between E5.2 and D1.3 is driven by a large negative enthalpy and its rate and equilibrium association constants are comparable to those observed in other antigen-antibody reactions. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…So what causes the reduction in the k on ? Previously, kinetic and structure studies of the anti-lysozyme antibody D1.3 have indicated that local conformational adaptation is responsible for the association rate (40). Furthermore, statistical thermodynamic analysis of the same antibody has shown that the binding effects can propagate to a subset of residues at distal sites when the binding sites include the region with conformational fluctuations (41).…”
Section: Discussionmentioning
confidence: 99%
“…So what causes the reduction in the k on ? Previously, kinetic and structure studies of the anti-lysozyme antibody D1.3 have indicated that local conformational adaptation is responsible for the association rate (40). Furthermore, statistical thermodynamic analysis of the same antibody has shown that the binding effects can propagate to a subset of residues at distal sites when the binding sites include the region with conformational fluctuations (41).…”
Section: Discussionmentioning
confidence: 99%
“…As for affinity studies, a number of data are now available on kinetic measurements of antigen-antibody interactions assessed by surface plasmon resonance (8,(19)(20)(21)(22). These studies show that equilibrium constants of these interactions vary from 10 6 to 10 11 with k ass values ranging from 10 3 to 10 6 and k diss ranging from 10 Ϫ3 to 10…”
Section: Discussionmentioning
confidence: 99%
“…An alternative possible explanation for the effect of mutations on the association state might be differential solvation or desolvation. It is known that solvent structure can exert a significant effect in macromolecular interactions (45). Solvent structure associated with the unusually exposed phenyl group of Phe-43 could be quite different from that with its valyl counterpart, and its rate of reorganization on binding to gp120 could then also be different.…”
Section: Discussionmentioning
confidence: 99%